Cold acclimation alleviates cold stress-induced PSII inhibition and oxidative damage in tobacco leaves. (31st December 2022) - Wei, Yanli; Chen, Hongzhi; Wang, Lu; Zhao, Qin; Wang, Di; Zhang, Tongen
ABSTRACT: This study aimed to explore how cold acclimation (CA) modulates cold stress in tobacco leaves and reveal the relationship between CA and cold stress resistance, and the mechanism of CA-induced plant resistance to cold stress. This study examined the effects of CA treatment (at 8–10℃ for 2 d) on the cold tolerance of tobacco leaves under 4°C cold stress treatment using seedlings without CA treatment as the control (NA). In both CA and NA leaves, cold stress treatment resulted in a decrease in maximum photochemical efficiency of PSII ( F v /F m ), increase in relative variable fluorescence ( V J ) at 2 ms on the standardized OJIP curve, inhibition of PSII activity, and impairment of electron transfer on the acceptor side. Besides increasing the malondialdehyde (MDA) content and electrolyte leakage rate, the cold stress exacerbated the degree of membrane peroxidation. The CA treatment also induced the accumulation of reactive oxygen species (ROS), including superoxide anion (O2 · − ) and H2 O2, and increased the activities of antioxidant enzymes, such as superoxide dismutase (SOD), peroxidase (POD), catalase (CAT) and ascorbic acid peroxidase (APX). The CA treatment also enhanced the accumulation of soluble sugar (SS) and soluble protein (SP), cyclic electron flow (CEF), and the proportion of regulatory energy dissipation Y(NPQ). Moreover, CA+ cold stress treatment significantly reduced CEF and Y(NPQ) in tobacco leaves than under NA+ cold stress treatment, thus significantly alleviating the degree of PSII photoinhibition. In conclusion, CA treatment significantly alleviated PSII photoinhibition and oxidative damage in tobacco leaves under cold stress treatment. Improvement in cold resistance of tobacco leaves is associated with the induction of antioxidant enzyme activity, accumulation of osmoregulation substances, and initiation of photoprotective mechanisms.